Blends of isotactic polypropylene and nitrile rubber : Effect of blend ratio on morphology, dielectric and mechanical properties - George Snoopy; Thomas Sabu; Varghese K T (Papers presented at the National Seminar on rubber blends at RRII, Kottayam, November 14, 1995, 1995)
The morphology, mechanical properties and electrical properties of a series of blends of isotactic polypropylene (PP) with nitrile rubber (NBR), prepared in a Brabender Plasticorder, were investigated with special reference to the effect of blend ratio. Dielectric and mechanical properties depended on blend ratio and blend morphology. Morphological observations of the blend showed a two phase system. NBR remained as a dispersed phase in a continuous PP matrix, till the NBR content in the blend increased upto 50 weight per cent. At 70 weight per cent of NBR, both NBR and PP formed continuous phases. The mechanical strength of NBR/PP blend depended on the strength of PP phase which, in turn, depended on the extent of crystallinity. The decrease in tensile strength,tear strength and hardness with increase in NBR content was due to the soft rubbery phase. Premitivity increased with increase in NBR content due to increase in orientation polarisation by the presence of increased C=N dipoles. Both dissipation factor and loss factor increased with NBR content due to increase in polarity. The change of dielectric properties was more sharp when NBR content in the blend was 70 weight per cent